BENTUK PENYAJIAN REOG PONOROGO DALAM ACARA TUJUH BELAS AGUSTUS DI DESA PARIT I/II KECAMATAN SUNGAI APIT KABUPATEN SIAK RIAU - Rhodiya Rhodiya; Syeilendra Syeilendra; Wimbrayardi Wimbrayardi (FBS Universitas Negeri Padang, 2013)
Abstract The purpose of this research was to describe the form of Reog Ponorogo in Tujuh Belas Agustus event in Desa Parit I/II Kecamatan Sungai Apit Kabupaten Siak Riau. The researcher did a field observation when the show was held in the afternoon. There were 8 people involved in the show, 6 people as the instrument players, 1 person as the singo barong player and I person as the topeng bujang player. The properties used were barongan dadak merak, kuda kepang, topeng bujang ganong. The music instruments were the gamelan such as kenong, gong, ketipung, kendang, slomfret. As the gamelan goes wilder, the singo barong will be more active in doing some attractions. Kata kunci : Bentuk, Penyajian, Reog, Ponorogo,Sidodadi